Dynamic latent variables path models: An alternative PLS estimation - Hans Gerhard Strohe (Universität Potsdam, Wirtschafts- und Sozialwissenschaftliche Fakultät, 1995)
In this paper a partial least squares (PLS) approach to dynamic modelling with latent variables is proposed. Let Y be a matrix of manifest variables and H the matrix of the corresponding latent variables. And let H = BH+ε be a structural PLS model with a coefficient matrix B. Then this model can be made a dynamic one by substituting for B a matrix F = B + CL containing the lag operator L. Then the structural dynamic model H = FH+ε is formally estimated like an ordinary PLS model. In an exploratory way the model can be used for forecasting purposes. The procedure is being programmed in ISP.
urn:nbn:de:kobv:517-opus-29498
Keywords: 330; PLS; dynamic models; path models